Analysis of transmit antenna selection/switch-and-examine combining over Nakagami-m fading channels - Tan, Beng Soon (2013)
In this paper, we analyze a diversity system with the transmit antenna selection (TAS) at the transmitter and the switch-and-examine combining (SEC) at the receiver over a Nakagami-m fading channel. This system has lower complexity as compared to the TAS schemes with maximum-ratio combining and generalized selection combining at the receiver. Furthermore, the TAS/SEC scheme requires a smaller number of branch estimations compared to the TAS/SC scheme. The performance of the TAS/SEC system with binary phase-shift keying over a Nakagami-m fading channel is examined. The expressions of the average output signal-to-noise ratio and bit-error rate are derived and presented.